Lifestyle Modifications for Migraine Management - Agbetou, Mendinatou; Adoukonou, Thierry (Frontiers in Neurology, 2022)
Migraine is a disabling disease that inflicts a heavy burden on individuals who suffer from it. Significant advances are being made in understanding the pathophysiology and treatment of the disease. The role of lifestyle modifications has become increasingly predominant. We reviewed the current and available data on the role of a healthy lifestyle in the management of migraine. Physical activity, management of obesity, a healthy diet, and a better lifestyle, such as adequate sleep and avoidance of drug abuse, significantly contribute to reducing the frequency and severity of attacks. It is important to consider these factors in the overall management strategies for migraine sufferers.